Nutritional analysis of rice field rat (Rattus rattus mindanensis) - Manuel, Jeehan Manalansan; Dumelod, Benelyn Domingo (Quezon City University of the Philippines Diliman, 2001)
The proximate composition and the mineral profile of the raw meat of rice field rat (Rattus rattus mindanensis) were determined and evaluated. The proximate analysis involved the determination of moisture content using the vacuum oven method, crude fat content using the Soxhlet extraction method, crude protein using the Kjeldahl method and ash content using the combustion or dry ashing method. The mineral analysis involved in the determination of the amount of calcium, sodium, potassium, magnesium, iron, zinc, copper, manganese, chromium and cobalt using the atomic absorption spectrometric method. The results showed that the proximate composition of the sample is comparable to most animal foods and animal products that are commonly consumed. The rice field rat is, indeed, an inexpensive meat substitute that can augment the protein requirements of people especially those with low purchasing powder and those suffering from protein-energy malnutrition. The absolute concentration of the minerals in the raw meat would remain the same when the meat is fried since minerals are not destroyed during cooking and are soluble only in water. However, the relative composition or percentages of the minerals would change due to moisture loss and shrinkage of the meat as effected by the meat treatment. The amount of calcium, sodium, potassium, magnesium, iron, zinc, copper and manganese provides only less than 20 percent of the RDA per serving portion assumed as 100 grams of the raw meat, fried and consumed. The mineral levels of of the sample are found to be comparable to most animal foods and animal products. The instruments used lack sensitivity to determine the exact level of chromium so that comparison with other animal foods and animal product could not be done. As for cobalt with no established RDA, the amount may be sufficient to meet the requirements for cobalt intake.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat -- Analysis; Rats